ANALISIS KEMAMPUAN MEMBACA DAN MENULIS MENGGUNAKAN METODE DEMONSTRASI PADA SISWA KELAS II A DI SDN 002 SUNGAI PINANG - Ramadhani, Bella; editor sistema 3; Alif Tunru, Andi (SISTEMA: Jurnal Pendidikan, 2024)
The main purpose of this study is for described reading and writing skill analysis by using demonstrate method. This research was doing by using qualitative descriptive analysis; this research also used flow model analysis proposed by Miles & Huberman, then validation test by using triangulation technique. Subject in this research was using purpose sampling is teacher who was teaching in class II A, students class II A and the students who couldn’t reading and writing well in SD Negeri 002 Sungai Pinang. The result of the research that; reading and writing skill of students’ class II A SD Negeri 002 Sungai Pinang good enough, but actually there are some students who was getting problems in basic of writing and reading. The problems in reading are: Reading too slowly, out of order and unclear intonations, the students having troubles when read consonant, the students couldn’t spell well, and letters or words are exchanged. The problems in writing are : the students write disorder letters, the letters are imperfect, the consistence of letters size, sometimes it could be big and small, there is no space, the letters position isn’t in line, the way of using pencils and wrong position for writing. The solution to handling this kind of problems are: doing private course for students who were getting problems in reading and writing, the teachers giving extra time to guide the students who were getting problem in reading and writing skills, teacher and parents are working together for monitoring the students improvement.